2020
DOI: 10.1017/cem.2020.438
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site intervention to improve emergency department care for patients who live with opioid use disorder: A quantitative evaluation

Abstract: Background Opioid use disorder is a major public health crisis, and evidence suggests ways of better serving patients who live with opioid use disorder in the emergency department (ED). A multi-disciplinary team developed a quality improvement project to implement this evidence. Methods The intervention was developed by an expert working group consisting of specialists and stakeholders. The group set goals of increasing prescribing of buprenorphine/naloxone and providing next day walk-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Although many studies have reported on ED-specific or region-based BUP programs, 17,[19][20][21][22] few studies have reported the practice patterns of individual ED physicians. Compared with a 2018 survey that found 7% of Canadian ED physicians prescribed BUP often or always, 28 a greater proportion of our respondents reported prescribing BUP once a month or more.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have reported on ED-specific or region-based BUP programs, 17,[19][20][21][22] few studies have reported the practice patterns of individual ED physicians. Compared with a 2018 survey that found 7% of Canadian ED physicians prescribed BUP often or always, 28 a greater proportion of our respondents reported prescribing BUP once a month or more.…”
Section: Discussionmentioning
confidence: 99%
“…At the system level, Alberta's Strategic Clinical Networks are mandated to address cross-systems issues with evidence-based solutions in collaboration with diverse stakeholders, to support data-driven decision making, improve population health and catalyze health equity (34). For instance, the Emergency Strategic Clinical Network built referral pathways between s emergency departments and addiction treatment clinics prior to the pandemic (35). At a provincial level, systems can embrace harm reduction and contextually tailored care with decriminalization of people who use substances (15,36) and clinical guidelines for safe supply (25) that systemically addresses stigma.…”
Section: Discussion: Outcomes Of Covid-19 Disruptionsmentioning
confidence: 99%
“…Retrospective studies relied on documentation of OUD in the medical record. 16,21,23 Opioid Withdrawal…”
Section: Opioid Use and Opioid Use Disordermentioning
confidence: 99%
“…Nine studies in which buprenorphine was administered in the emergency department measured symptom severity via the Clinical Opiate Withdrawal Scale (COWS). 11,16,17,21,[23][24][25][26] COWS cut scores for buprenorphine induction ranged from > _5 24,25 to a score of > _36 corresponding to severe opioid withdrawal. 11…”
Section: Opioid Use and Opioid Use Disordermentioning
confidence: 99%